Internet of Things (IoT) Security Challenges and Solutions: A Systematic Literature Review - Ali, R.F. (Springer Science and Business Media Deutschland GmbH, 2021)
The Internet of Things (IoT), often known as the Internet of Everything, is a new technological paradigm visualized as a worldwide network of interconnected machines. IoT brings another dimension into Information Technology (IT), where machines can communicate with various machines and humans. Researchers and IT industry produced various IoT devices, architectures. Different ways are introduced to implement and use IoT concepts. IoT is getting more intention in ideas like smart homes and smart cities, raising security concerns. This article aims to gather the reported security issues, the classification of those issues, and the solutions that were provided against those IoT security issues. Â© 2021, Springer Nature Singapore Pte Ltd.